Mechanisms of proton inhibition and sensitization of the cation channel TRPV3 - Wang, Haiyuan (J Gen Physiol, 2020)
TRPV3 is a temperature-sensitive, nonselective cation channel expressed prominently in skin keratinocytes. TRPV3 plays important roles in hair morphogenesis and maintenance of epidermal barrier function. Gain-of-function mutations of TRPV3 have been found in both humans and rodents and are associated with hair loss, pruritus, and dermatitis. Here, we study the mechanisms of acid regulation of TRPV3 by using site-directed mutagenesis, fluorescent intracellular calcium measurement, and whole-cell patch-clamp recording techniques. We show that, whereas extracellular acid inhibits agonist-induced TRPV3 activation through an aspartate residue (D641) in the selectivity filter, intracellular protons sensitize the channel through cytoplasmic C-terminal glutamate and aspartate residues (E682, E689, and D727). Neutralization of the three C-terminal residues presensitizes the channel to agonist stimulation. Molecular dynamic simulations revealed that charge neutralization of the three C-terminal residues stabilized the sensitized channel conformation and enhanced the probability of α-helix formation in the linker between the S6 transmembrane segment and TRP domain. We conclude that acid inhibits TRPV3 function from the extracellular side but facilitates it from the intracellular side. These novel mechanisms of TRPV3 proton sensing can offer new insights into the role of TRPV3 in the regulation of epidermal barrier permeability and skin disorders under conditions of tissue acidosis.